A Novel Ultrasound-guided Forearm Continuous Peripheral Nerve Block Technique Using Bidirectional Hydrodissection - Kazuho Aizawa, MD, PhD; Makoto Motomiya, MD, PhD; Mitsutoshi Ota, MD, PhD; Naoya Watanabe, MD, PhD; Norimasa Iwasaki, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Summary:. In hand surgery, postoperative rehabilitation is essential for achieving optimal functional recovery. Although continuous peripheral nerve block at the forearm level is considered a useful method for maintaining motor function while relieving pain, it has not been widely adopted due to concerns about invasiveness and the reliability of the technique. We have developed a simplified, reliable, and safe continuous peripheral nerve block technique by applying the parallel method used in conventional ultrasound-guided nerve blocks. First, hydrodissection in the axial view creates space around the target nerve, allowing for easy identification of nerves that are difficult to visualize in the sagittal view. Additionally, this space serves as a target for catheter placement, enabling the introducer needle to be advanced safely into the area surrounding the nerve in the sagittal view. We believe that this novel approach will enable more effective postoperative rehabilitation in hand surgery.